Trio-Based Deep Sequencing Reveals a Low Incidence of Off-Target Mutations in the Offspring of Genetically Edited Goats - Li, Chao; Zhou, Shiwei; Li, Yan; Li, Guanwei; Ding, Yige; Li, Lan; Liu, Jing; Qu, Lei; Sonstegard, Tad; Huang, Xingxu; Jiang, Yu; Chen, Yulin; et al. (Frontiers in Genetics, 2018)
Unintended off-target mutations induced by CRISPR/Cas9 nucleases may result in unwanted consequences, which will impede the efficient applicability of this technology for genetic improvement. We have recently edited the goat genome through CRISPR/Cas9 by targeting MSTN and FGF5, which increased muscle fiber diameter and hair fiber length, respectively. Using family trio-based sequencing that allow better discrimination of variant origins, we herein generated offspring from edited goats, and sequenced the members of four family trios (gene-edited goats and their offspring) to an average of ~36.8× coverage. This data was to systematically examined for mutation profiles using a stringent pipeline that comprehensively analyzed the sequence data for de novo single nucleotide variants, indels, and structural variants from the genome. Our results revealed that the incidence of de novo mutations in the offspring was equivalent to normal populations. We further conducted RNA sequencing using muscle and skin tissues from the offspring and control animals, the differentially expressed genes (DEGs) were related to muscle fiber development in muscles, skin development and immune responses in skin tissues. Furthermore, in contrast to recently reports of Cas9 triggered p53 expression alterations in cultured cells, we provide primary evidence to show that Cas9-mediated genetic modification does not induce apparent p53 expression changes in animal tissues. This work provides adequate molecular evidence to support the reliability of conducting Cas9-mediated genome editing in large animal models for biomedicine and agriculture.